Applying Whispering Game in Developing Listening Comprehension of Grade Eleven Students of SMAN 7 Palu - Ewis Febriani; Sudarkam R. Mertosono; Desrin Lebagi; Mukrim Mukrim (Universitas Cokroaminoto Palopo, 2024)
This purpose of this research is to investigate the effectiveness of using the whispering game in developing listening comprehension of grade eleven students of SMAN 7 Palu. This research applied a pre-experimental research approach. The population for this research was the eleventh grade students at SMAN 7 Palu, which consisted of ten classes, with 36 students picked from class XI 3 using purposive sampling. The instrument used in this research was a listening test with audio. Researchers employed pre-test and post-test methods to collect data. The collected data was analyzed using SPSS Version 23. The results showed that the mean score of the pre-test was (61.30) and post-test was (77.59). According to the findings of the t-test simple independence test, the sig (2 tailed) (0.000) value is lower than 0.05. This demonstrates that the alternative hypothesis is accepted. As a result, the whispering game is effective in developing listening comprehension of grade eleven students of SMAN 7 Palu.